COMPARE THE ANALGESIC EFFICACY OF 0.25% BUPIVACAINE AND 0.25% BUPIVACAINE WITH 0.9 μG/KG DEXMEDETOMIDINE IN TAP BLOCK - VINAYAK GOUR; SEVRAS HINGWE; CHANDRAKANT; JYOTI RAGHUWANSHI (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The transversus abdominis plane (TAP) block is a relatively new regional anesthesia technique that provides analgesia to the parietal peritoneum as well as the skin and muscles of the anterior abdominal wall. Despite a relatively low risk of complications and a high success rate using modern techniques, TAP blocks remain overwhelmingly underutilized. The objective is to compare the analgesic efficacy of 0.25% bupivacaine and 0.25% bupivacaine with 0.9 μg/kg dexmedetomidine in TAP block as a part of a multimodal analgesia regimen for post-cesarean delivery pain management. Methods: Patients more than 18 years old posted for elective/emergency caesarean section in ABVGMC, Vidisha, Madhya Pradesh. After approval from the institutional ethical committee and written informed patients consent, 20 each pregnant women were included in the both study group. Group A: TAP block with 0.25% bupivacaine 20 mL each side Group B: TAP block with 0.25% bupivacaine with 0.9 μg/kg dexmedetomidine 20 mL each side. We studied TAP block in patients posted for elective caesarean section. Results: The women received 0.25% bupivacaine or 0.25% bupivacaine with 0.9 μg/kg dexmedetomidine. The median visual analogue scale (VAS) for pain was significantly higher in the bupivacaine Group A at 12 h with compare to Group B. Overall, there was no difference in VAS score at 0.5, 2, 4, 6, and 24 h demands between the two groups. The mean time to first rescue analgesia in Group A was 14.6±5.5 h and in Group B was 16.8±4.2 h. Conclusion: We conclude that the using dexmedetomidine as an additive to bupivacaine in ultrasound-guided TAP block for elective/emergency caesarean section provides prolonged duration of post-operative analgesia, and lowered VAS pain scores. The addition of dexmedetomidine to bupivacaine also reduced the total dose of opioid requirement in the first 24 h after caesarean section.